Revision of the black fly genus Gigantodax (Diptera, Simuliidae). Bulletin of the AMNH - Wygodzinsky, Pedro W.; Coscarón, Sixto. ([New York] : American Museum of Natural History, 1989)
269 p. : ill., maps 26 cm. Includes bibliographical references (p. 268-269). "A taxonomic study of the genus Gigantodax Enderlein is presented, including keys, descriptions, redescriptions, discussions, illustrations, and distributional and biological information. Gigantodax is the largest genus of Neotropical Prosimuliini, with 64 species extending along the Andean system from Mexico to Tierra del Fuego. Because most species described herein were collected by the authors from breeding sites, the morphology of immature and adult stages is presented. The species are tentatively arranged into eight groups as follows: (1) cortesi group; G. cortesi n. sp. (N Chile), G. jatunchuspi n. sp. (N Chile), G. punapi n. sp. (N Chile, NW Argentina, and Bolivia), G. chacabamba (Peru). (2) igniculus group; G. carmenae n. sp. (Patagonian Andes), G. igniculus Coscarón and Wygodzinsky. (3) minor group; G. araucanius (Edwards), G. eremicus n. sp. (N Chile), G. minor n. sp. (central Chile and Patagonian Andes), G. bolivianus Enderlein. (4) multifilis group; G. multifilis n. sp. (Ecuador). (5) brophyi group; G. brophyi (Edwards), G. rufidulus n. sp. (Patagonian Andes), G. antarcticus (Bigot), G. trifidus n. sp. (central Chile and Patagonian central Andes of Argentina), G. femineus (Edwards), G. marginalis (Edwards), G. kuscheli Wygodzinsky, G. luispenai n. sp. (central Chile), G. chilensis (Philippi), G. flabellus (Venezuela and Ecuador), G. awa n. sp. (east slope Peruvian Andes), G. paramorum n. sp. (Colombia), G. viannamartinsi Ramirez Perez, G. ortizi Wygodzinsky, G. multituberculatus n. sp. (Colombia and Ecuador), G. patihuaycensis n. sp. (east slope Peruvian Andes), G. laevigatus n. sp. (Ecuador), G. zumbahuae n. sp. (Ecuador). (6) cilicinus group (with three subgroups); subgroup A; G. fulvescens (Blanchard), G. shannoni (Edwards), G. destitutus n. sp. (Venezuela and Colombia), G. basinflatus n. sp. (Colombia and Ecuador), G. mariobordai n. sp. (Bolivia), G. incomitatus n. sp. (Venezuela); subgroup B; G. pennipunctus ...